An Overview of the Challenges and Resources Special Education Professionals Reported During the Early COVID-19 Pandemic - Kamei, Ai; Lubniewski, Kathryn; Littin, Stacy Lauderdale; Mcarthur-Amedeo, Carol; Haspel, Mary; Harriott, Wendy (Journal of the American Academy of Special Education Professionals, 2024)
With the onset of COVID-19, school districts were forced to rapidly engage in planning and development of resources for remote instruction during spring of the 2020 school year, and many special education professionals reported difficulties meeting student needs. In order to portrait the initial challenges and concerns related to remote instruction faced by these professionals, data were collected from a Council for Exceptional Children (CEC) public forum from March 7 to April 21 of 2020. Content analysis method was used to determine themes related to challenges with meeting the needs of students with special needs and resources utilized to overcome these challenges. From 638 entries, five major issues were identified: (a) challenges with using instructional technologies appropriately, (b) students’ engagement, (c) collaboration with families, (d) exacerbated inequity, and (e) needs for clear guidance during a crisis. Areas of improvement and future implications for remote learning for special education are discussed.